2011
DOI: 10.5216/pat.v41i3.9650
|View full text |Cite
|
Sign up to set email alerts
|

Arranjo De Plantas Para Diferentes Híbridos De Milho

Abstract: INTRODUÇÃOO rendimento de grãos do milho é uma variável complexa e depende da interação entre fatores genéticos, ambientais e de manejo. No Brasil, o rendimento médio do milho é muito baixo, em decorrência de fatores ligados à fertilidade do solo, arranjo espacial de plantas (Fancelli & Dourado Neto 2004),

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
12
1
8

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 13 publications
(22 reference statements)
6
12
1
8
Order By: Relevance
“…The proximity between treatments D and H can also be explained because the treatments had the same spacing, where the spacing of 80 cm between rows influenced positively the mass of ear with and without husk, the ear diameter and the number of grains per ear. These results are contrary to those found by Kappes et al (2011), which showed that the use of the reduced spacing (45 cm) was advantageous, increasing corn productivity by 15%, compared to the 90 cm row spacing. However, the row spacing did not significantly influence the mass of 1000 grains and productivity, which together represented 32% of the variation in principal components analysis.…”
Section: Treatmcontrasting
confidence: 99%
See 1 more Smart Citation
“…The proximity between treatments D and H can also be explained because the treatments had the same spacing, where the spacing of 80 cm between rows influenced positively the mass of ear with and without husk, the ear diameter and the number of grains per ear. These results are contrary to those found by Kappes et al (2011), which showed that the use of the reduced spacing (45 cm) was advantageous, increasing corn productivity by 15%, compared to the 90 cm row spacing. However, the row spacing did not significantly influence the mass of 1000 grains and productivity, which together represented 32% of the variation in principal components analysis.…”
Section: Treatmcontrasting
confidence: 99%
“…The use of suitable spacings for each cultivar in each region can increase corn production components and productivity. Despite the advantages of using narrower spacing (Modolo, Carnieletto, Kolling, Trogello, & Sgarbossa, 2010;Lana et al, 2014a), researchers have also demonstrated that corn crops, using spacings of up to 90 cm between rows, presented similar or higher agronomic and productive parameters compared to reduced spacings of up to 40 cm (Deparis, Lana, & Frandoloso, 2007;Kappes et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The use of higher plant densities at smaller spacings allows a higher interception of photosynthetically active radiation, promoting higher grain yield (SANGOI et al, 2010). On the other hand, this strategy leads to lodging (KAPPES et al, 2011) and self-shading of plants, with a reduced yield, which can be overcome using plant regulators.…”
Section: Introductionmentioning
confidence: 99%
“…Híbridos de milho modernos apresentam menor porte, menor área foliar e ciclo precoce, que favorece o desempenho produtivo da lavoura, pelo incremento no índice de colheita (Kappes et al, 2011).…”
unclassified